Understanding automotive electronics - Ribbens, William B.; Mansour, Norman P. (Amsterdam ; Boston : Newnes, 2003)
In addition, the new edition explains new electronically controlled vehicle motion control systems including advanced suspension, electronically controlled electric power steering, 4-wheel steering and electronically controlled electric brakes. The braking systems are part of an integrated motion control system that couples ABS brakes; traction control and variable vehicle dynamics for enhanced stability are also described. The development of hybrid/electric vehicles and their associated electronic control/monitoring systems as well as the new technologies incorporated into conventional gasoline and diesel-fueled engines are also discussed. *Extensive revision of a popular text *Covers the shift from 14-volt to 42-volt systems *Includes information on future automotive electronic systems.
Automotive Fundamentals; The Systems Approach to Control and Instrumentation; Electronics Fundamentals; Microcomputer Instrumentation and Control; The Basics of Electronic Engine Control; Sensors and Actuators; Digital Engine Control System; Vehicle Motion Control; Automotive Instrumentation; Diagnostics; Future Automotive Electronic Systems.
Includes index.
Keywords: Automobiles -- Electronic equipment; Electronic books